Visitor Management Concept Through Carrying Capacity Analysis In Forest Recreation - Aziean Jamin; Fitri Rahmafitria (Universitas Pendidikan Indonesia, 2022)
A b s t r a c tKawah Putih Forest Recreation (KPFR) is a tourism area with beautiful and unique scenery, functioning as biodiversity conservation and protection of Presbylis comata, an endemic primate of West Java. Because of its complex function, the use of the area for tourism should consider carrying capacity aspect. Carrying capacity is identified from three factors; those are physical carrying capacity (PCC), real carrying apacity (RCC) and effective carrying capacity (ECC). The calculation resulted from these three factors are then compared to the actual condition in KPFR. This research showed that physically the crater area of KPFR could accommodate 986 visitor/day (PCC). The result also showed that according to the specific characteristic of the area KPFR could accommodate 255 visitors/ day (RCC), while in its management capacity, the mode of local transportation in KPFR only able to carry 98 visitors/ day (ECC). A b s t r a kHutan Rekreasi Kawah Putih (KPFR) merupakan kawasan wisata dengan pemandangan yang indah dan unik, berfungsi sebagai konservasi keanekaragaman hayati dan perlindungan Presbylis comata, primata endemik Jawa Barat. Karena fungsinya yang kompleks, maka pemanfaatan kawasan untuk pariwisata harus memperhatikan aspek daya dukung. Daya dukung diidentifikasi dari tiga faktor; yaitu daya dukung fisik (PCC), daya dukung nyata (RCC) dan daya dukung efektif (ECC). Hasil perhitungan dari ketiga faktor tersebut kemudian dibandingkan dengan kondisi sebenarnya di KPFR. Hasil penelitian menunjukkan bahwa secara fisik kawasan kawah KPFR mampu menampung 986 pengunjung/hari (PCC). Hasil penelitian juga menunjukkan bahwa sesuai dengan karakteristik spesifik kawasan KPFR mampu menampung 255 pengunjung/hari (RCC), sedangkan dalam kapasitas pengelolaannya, moda transportasi lokal di KPFR hanya mampu mengangkut 98 pengunjung/hari (ECC).